2012
DOI: 10.1167/iovs.11-8783
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Base Substitution in the Seed Region of miR-184 Causes EDICT Syndrome

Abstract: The single-base-pair substitution in the seed region of miR-184 is responsible for the disease phenotype observed in EDICT syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 42 publications
3
95
0
Order By: Relevance
“…Hughes et al identified a mutation in the central nucleotide of the seed region of MIR184 as the cause of keratoconus and early-onset anterior polar cataracts in a large Irish family, although the underlying pathogenic mechanism was not extensively delineated (36). Iliff et al reported the same mutation as the cause of EDICT syndrome, an autosomal dominant anterior segment dysgenesis syndrome characterized by endothelial dystrophy, iris hypoplasia, congenital cataract and stromal thinning (37). A further two novel heterozygous substitution variants, neither of which were located within the seed region, were later identified in MIR184 in two patients with isolated keratoconus (38).…”
Section: Discussionmentioning
confidence: 97%
“…Hughes et al identified a mutation in the central nucleotide of the seed region of MIR184 as the cause of keratoconus and early-onset anterior polar cataracts in a large Irish family, although the underlying pathogenic mechanism was not extensively delineated (36). Iliff et al reported the same mutation as the cause of EDICT syndrome, an autosomal dominant anterior segment dysgenesis syndrome characterized by endothelial dystrophy, iris hypoplasia, congenital cataract and stromal thinning (37). A further two novel heterozygous substitution variants, neither of which were located within the seed region, were later identified in MIR184 in two patients with isolated keratoconus (38).…”
Section: Discussionmentioning
confidence: 97%
“…81 Of particular relevance, linkage analysis in combination with nextgeneration sequencing identified a heterozygous mutation in mir-184 in two families with dominant congenital cataract associated with a corneal phenotype that in some cases was consistent with KC. 50,82,83 To establish whether mutations in mir-184 were associated with KC, mir-184 was subsequently screened in a cohort of 780 KC patients. 84 Rare variants were identified in two (0.25%) patients, but the variants did not fully segregate with disease, suggesting that mir-184 variants are not a common cause of isolated KC.…”
Section: Geneticsmentioning
confidence: 99%
“…In spite of their importance in gene-expression regulation, few mutations of individual miRNAs have been found to cause Mendelian inherited diseases in humans, raising doubts about their importance in normal development and functions, and whether mutations in a miRNA can have significant functional impact to cause Mendelian inherited diseases, including IRD. Recently, a point mutation in the seed sequence of miR-184 was reported to cause familial keratoconus with cataract (5) and an anterior-segment dysplasia syndrome with endothelial dystrophy, iris hypoplasia, congenital cataract, and stromal thinning (6), suggesting that miR-184 is required for anterior-segment development and function, and proving that mutations in an individual miRNA can cause inherited ocular disease in humans. In mice, Lumayag et al demonstrated that inactivation of the miR-183/96/ 182 cluster gene causes syndromic IRD with multisensory defects (7), suggesting that defects in miRNA genes can cause IRD in mammals.…”
mentioning
confidence: 99%